PELATIHAN DAN PENINGKATAN KAPASITAS KINERJA PERANGKAT KAMPUNG REMPAK BERSAMA DENGAN YAYASAN MITRA DESA MEMBANGUN UNTUK PENGEMBANGAN KABUPATEN SIAK - Bedasari, Hafzana; Fuaduddin, Fuaduddin; Ramadhani, Della Zullinda; Nurhalizah, Risma; Novitri, Cahyani Ayu; Putri, Annisa Komala; Putri, Amelia; Vebrinda, Arizta Zita; Trikurnia, Repti; Nasyabila, Salfa; Zulkarnaen, Ahmad Sulthan; Muhti, Rayi Abhinaya Januar; Anandika, Naufal Muhammad (Universitas Mataram, 2025)
Training on Understanding Main Duties and Functions for the Officials of Kampung Rempak was conducted as an effort to enhance the capacity and professionalism of the village government apparatus in delivering services to the community. The training aimed to provide a comprehensive understanding to the Penghulu, Kerani, Juru Tulis, and Kepala Dusun in Kampung Rempak. The objective of this training is to strengthen the understanding of village officials regarding their main duties and functions (tupoksi), thereby improving performance and the quality of public services. Furthermore, the training aims to foster professional attitudes among village officials, enhance coordination between village apparatus, and encourage innovation in providing public services aligned with local needs and digital era developments. The training began with the delivery of materials accompanied by case studies. Such an approach was implemented to ensure a deeper understanding of the material and to encourage active participation from the participants. The results of the training indicate that participants gained a strong understanding of the fundamental aspects required to improve governance and development in Kampung Rempak, while also supporting the creation of more optimal services that align with community expectations. The activity also fostered awareness of the importance of coordination and synergy among Kampung Rempak officials in carrying out their respective roles and functions. Additionally, participants developed new skills in managing government administration more effectively and efficiently, and were encouraged to create innovative ideas that can be implemented in providing public services tailored to local community needs. The outcomes of this training are expected to make a tangible contribution to improving governance, village development, and public service delivery in Kampung Rempak, making them more effective and sustainable.